Manganese Toxicity: Free amino acids in the striatum and olfactory bulb of the mouse - Bonilla, Ernesto; Arrieta, Arelis; Castro, Fidel; Dávila, José Omar; Quiroz, Iris (Investigación Clínica, 2013)
Â  We studied the levels of twenty two free amino acids in the striatum and olfactory bulb of mice treated during nine weeks with daily intraperitoneal injections of manganese chloride at a concentration of 5.0 mg Mn+2Â¡kg body weight. In the olfactory bulb the contents of alanine, a-amino-n-butyrate. arginine. asparagine, aspartate, citrulline, GABA, glutamate, glycine, isoleucine, leucine methionine, phenylalanine, serine,threonine, tyrosine, and valine were diminished. No alterations were observed in the concentrations of free amino acids in the striatum of Mn-treated mice. The changes detected in the olfactory bulb merit a thorough evaluation in order to determine its importance on the pathophysiology of manganese poisoning.